Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan “Cream cheese “ Berbahan Dasar Santan Sebagai Substitusi - Salim, Chaerul; Wijayanto, Dedy; Pramudito, Pramudito (Jurnal Pemberdayaan Pariwisata; Vol 2 No 1 (2020): Jurnal Pemberdayaan Pariwisata, 2020)
All cheese is made from milk but there are various kinds of milk as raw material used to make cheese. Cream cheese is soft cheese that results from the addition of instant coconut milk. With the hope that if the level of consumer preference is exceeded, cream cheese products from instant coconut milk can be mass produced. The aim is to find out how the reaction of people who like cheese to the level of preference and the possibility of mass production. The method in this study uses a trial or experimental method approach. with a sample of 21 respondents taken randomly. Result, in terms of taste, texture, and color as well as knowing the presence or absence of differences in cream cheese products made from coconut milk in terms of taste, texture and color, therefore the results of the calculation and assessment of comparisons between control products and the treatment carried out by panelists on products that are in terms of texture, color, and taste.